2013
DOI: 10.1371/journal.pone.0070915
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Children’s Behavioral Tendency toward Social Indirect Reciprocity

Abstract: Social indirect reciprocity seems to be crucial in enabling large-scale cooperative networks among genetically unrelated individuals in humans. However, there are relatively few studies on social indirect reciprocity in children compared to adults. Investigating whether young children have a behavioral tendency toward social indirect reciprocity will help us understand how and when the fundamental ability to form cooperative relationships among adults is acquired. Using naturalistic observation at a nursery sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 65 publications
0
22
0
1
Order By: Relevance
“…Studies have also revealed that it is not before 5-6 years of age that children spontaneously reciprocate recipients who have previously shown prosocial behaviour toward a third party (Kato-Shimizu et al, 2013), thus supporting the possibility that indirect reciprocity may be a late developing aspect of prosocial behaviour. Interestingly, the concept of reputation, which is strongly linked to indirect reciprocity, seems to emerge around 5-6 years of age too.…”
Section: Discussionmentioning
confidence: 79%
“…Studies have also revealed that it is not before 5-6 years of age that children spontaneously reciprocate recipients who have previously shown prosocial behaviour toward a third party (Kato-Shimizu et al, 2013), thus supporting the possibility that indirect reciprocity may be a late developing aspect of prosocial behaviour. Interestingly, the concept of reputation, which is strongly linked to indirect reciprocity, seems to emerge around 5-6 years of age too.…”
Section: Discussionmentioning
confidence: 79%
“…According to the perspective of indirect reciprocity, people are thought to have a strong motivation to build a good reputation in social exchange domains in order to elicit favors from third parties, thus people become sensitive to monitoring by others. Consistent with this notion, studies have shown that people tend to base their behaviors on how others have behaved in the past ( Wedekind and Milinski, 2000 ) and that generous people receive more assistance from third-parties ( Kato-Shimizu et al, 2013 ). Signaling theory proposes that people can use costly signals, such as by giving generous allocations to others, to honestly signal their cooperative nature.…”
Section: Introductionmentioning
confidence: 89%
“…Call, 2009;Carpenter, 2009), and are especially attracted to social stimuli (e.g. Cohen & Cashon, 2006;Keen, 2003). Like other social species, humans are motivated to be with their conspecifics and likely evolved the cognitive skills to relate to others both in positive ways (e.g.…”
Section:  Conclusionmentioning
confidence: 99%